Conscientious objection as structural violence in the voluntary termination of pregnancy in Chile - Montero, Adela; Ramirez-Pereira, Mirliana; Robledo, Paz; Casas, Lidia; Vivaldi, Lieta; Gonzalez, Daniela (Frontiers in Psychology, 2022)
Introduction: After three decades of the absolute prohibition of abortion, Chile enacted Law 21,030, which decriminalizes voluntary pregnancy termination when the person is at vital risk when the embryo or fetus suffers from a congenital or genetic lethal pathology, and in pregnancy due to rape. The law incorporates conscientious objection as a broad right at the individual and institutional levels. Objectives: To explore the exercise of conscientious objection in public health institutions, describing and analyzing its consequences and proposals to prevent it from operating as structural violence. Material and Method: qualitative, post-positivist design. At the national level, according to the chain technique, those who were identified as key actors due to their direct participation in implementing the law were included. Grounded theory was used to analize the information obtained through a semi-structured interview. The methodological rigor criteria of transferability or applicability, dependability, credibility, auditability, and theoretical-methodological adequacy were met. Results: data from 17 physicians, five midwives, six psychologists, eight social workers, two nursing technicians, and one lawyer are included. From an inductive process through open coding, conscientious objection as structural violence and strategies to minimize the impact of objection emerge as meta-categories. The first meta-category emerges from the barriers linked to the implementation of the law, the infringement of the rights of the pregnant person, and pseudo conscientious objection, affecting timely and effective access to pregnancy termination. The second meta-category emerges as a response from the participants, proposing strategies to prevent conscientious objection from operating as structural violence. Conclusions: Conscientious objection acts as structural violence by infringing the exercise of sexual and reproductive rights. The State must fulfill its role as guarantor in implementing public policies, preventing conscientious objection from becoming hegemonic and institutionalized violence.